Government deficit, ex post real long-term interest rates and causality - CEBULA, R.J. (PSL Quarterly Review, 2013)
A number of empirical studies have investigated the impact of the federal Government budget deficit on interest rates in the US with most of them concluding that it is positive and significant on long-term interest rates. Both the IS/LM and the loanable funds frameworks through which this relationship is usually couched imply that causality flows from increased deficits to interest rates. The present work argues that the direction of causality may well be the reverse, that is real long-term interest rates may cause the budget deficit. The author offers two reasons to support this hypothesis. First, much or the Government’s debt is financed or refinanced in just a few short years. Second, according to conventional macroeconomic theory, a rise in the real interest rate should lead to a fall in real economic growth. A multivariate causality test is employed to determine the direction of causality among the real long-term interest rate, the unemployment rate and the structural deficit. JEL Codes: H6, E43